Compositional characterization of V-type candidate asteroids identified using the MOVIS catalogue. Issue 3 (25th July 2019) - Medeiros, H; de León, J; Lazzaro, D; Popescu, M; Lorenzi, V; Pinilla-Alonso, N; Landsman, Z; Rizos, J L; Morate, D
ABSTRACT: The main objective of this work is to compositionally analyse the visible to near-infrared spectra of a total of six V-type candidates identified using the MOVIS ( Y - J ) versus ( J - Ks ) colour–colour plot and located outside the Vesta collisional family. We obtained visible and near-infrared spectra of these asteroids using the 2.54m Isaac Newton Telescope, the 2.5m Nordic Optical Telescope, and the 3.58m Telescopio Nazionale Galileo, all located at the El Roque de Los Muchachos Observatory (La Palma, Spain), as well as the 3.0m NASA Infrared Telescope Facility, located at the Mauna Kea Observatory in Hawaii. We computed several diagnostic spectral parameters (slopes, band centres, band depths, band area ratio, or BAR) and compared them to the ones known for HED meteorites and (4) Vesta. The taxonomic classification confirmed five out of the six candidates as V-types, leading to an identification success rate about 83 per cent. In general, the spectral parameters obtained for the five V-types are in good agreement with those of HED meteorites and (4) Vesta. The exception is asteroid (2452) Lyot, a V-type in the outer belt, located very close to (1459) Magnya, but showing distinct [Wo] and [Fs] molar contents both from Magnya and Vesta, pointing toward a diogenitic compostion. We also studied the dependency of the BAR parameter on the way it is computed (removing or not the continuum), the spectral slope, and the last point used to delimit the right wing of the absorption band at 2 μm.